THE COMPANIES LISTED IN IDX30 BANKING SUB-SECTOR PERFORMANCE: DIVIDEND PAYOUT RATIO, PRICE EARNINGS RATIO, PRICE BOOK VALUE RATIO AND EARNING PER SHARE ON COMPANIES STOCK PRICE IN 2017-2021 - Amelia, Tifa Noer (Proceeding International Seminar of Islamic Studies, 2023)
This study was conducted to determine whether there is a significant effect of Dividend Payout Ratio (DPR), Price Earnings Ratio (PER), Price Book Value (PBV), and Earning Per Share (EPS) on the Stock Price of Companies Listed in IDX30 Banking Sub-Sector Period 2017-2021. The population in this study is companies listed on the Indonesia Stock Exchange which are in Index 30 during the period 2017–2021. This research used purposive sampling in choosing financials sector companies with sub-sector banks. The result shows that partially DPR, PBV and EPS can affect the stock price. PER was not affecting Stock price.